2005
DOI: 10.1093/humrep/dei091
|View full text |Cite
|
Sign up to set email alerts
|

ICSI in cases of sperm DNA damage: beneficial effect of oral antioxidant treatment

Abstract: Oral antioxidant treatment appears to improve ICSI outcomes in those patiens with sperm DNA damage, in whom this treatment reduces the percentage of damaged spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(103 citation statements)
references
References 32 publications
5
90
0
5
Order By: Relevance
“…The data obtained here illustrate clearly a marked improvement in the pregnancy and implantation rates at post-treatment ICSI cycle, which is most likely mediated by enhancement in sperm DNA integrity [26] [56]. This is concurrent with the observations reported by some studies [33] [34] [46]. Showell et al [28] published the Cochrane review on the basis of meta-analysis of 34 trials that included 2876 couples evaluating the effect of oral supplementation with antioxidants for male partners of couples undergoing ART.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The data obtained here illustrate clearly a marked improvement in the pregnancy and implantation rates at post-treatment ICSI cycle, which is most likely mediated by enhancement in sperm DNA integrity [26] [56]. This is concurrent with the observations reported by some studies [33] [34] [46]. Showell et al [28] published the Cochrane review on the basis of meta-analysis of 34 trials that included 2876 couples evaluating the effect of oral supplementation with antioxidants for male partners of couples undergoing ART.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike, Tremellen et al [34] and Greco et al [46] studies found no effect of oral antioxidant supplements with Menevit and a combined Vitamin C + Vitamin E respectively, on embryo development despite a significant reduction in sperm DNA damage and a boost in pregnancy rates. Keeping in mind evidences supported above, it would be expected that if sperm chromatin is unable to decondense after entering the ooplasma, fertilization or post-fertilization failure could occur due to defective sperm DNA namely DNA fragmentation.…”
Section: Discussionmentioning
confidence: 85%
“…Oxidative stress is known to be an important factor that causes male infertility by damaging sperm DNA [606162]. Greco et al [63] found that patients who took antioxidants before an ICSI procedure did not show differences in the fertility rate, cleavage rate, or embryo morphology, but had higher clinical pregnancy and implantation rates. However, Tremellen et al [64] argued that the positive effects of antioxidant therapy on SDF caused by reactive oxygen species are limited and that sperm DNA damage remains high in many patients even after treatment.…”
Section: Treatment Strategies For Patients With High Levels Of Sdfmentioning
confidence: 99%
“…The results showed that antioxidants might have increased clinical pregnancy rates [odds ratios (OR): 3.43, P < 0.0001, 7 RCTs, 522 men] and live birth rates (OR: 4.21, P < 0.0001, 4 RCTs, 277 men), but these evidences were graded low. Representative oral antioxidant therapies are vitamin C alone (400-1000 mg/ day) [98] and a combination of vitamins C and E [99,100]. Vitamins C and E work synergistically, and many studies on the positive effect of combined antioxidants on reducing DNA fragmentation and increasing the clinical pregnancy rate have been reported.…”
Section: Oral Antioxidant Therapymentioning
confidence: 99%